2014
DOI: 10.1007/s00441-014-2054-y
|View full text |Cite
|
Sign up to set email alerts
|

Localization of juxtacrine factor ephrin-B2 in pituitary stem/progenitor cell niches throughout life

Abstract: We have recently reported that Sox2-expressing pituitary stem/progenitor cells contact each other via a tight-junction protein CAR to form stem/progenitor cell niches in the marginal cell layer facing the lumen and in the clusters scattered in the parenchyma of the anterior lobe. However, the microenvironment of the niche for the maintenance of stem cell function in the pituitary remains obscure. In this study of pituitary stem/progenitor cell niches, we have attempted to identify the expression of juxtacrine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…Interestingly, we found PROP1 DNA binding sites in genes of Eph family suggesting the possibility of direct regulation. Taken together, these data support the idea that ephrin signaling is involved in regulation of the pituitary stem cell niche (119), but further studies are needed to demonstrate a functional role.…”
Section: Cell Signaling Pathways Regulating Pituitary Stem Cellssupporting
confidence: 76%
See 1 more Smart Citation
“…Interestingly, we found PROP1 DNA binding sites in genes of Eph family suggesting the possibility of direct regulation. Taken together, these data support the idea that ephrin signaling is involved in regulation of the pituitary stem cell niche (119), but further studies are needed to demonstrate a functional role.…”
Section: Cell Signaling Pathways Regulating Pituitary Stem Cellssupporting
confidence: 76%
“…The ephrin-A5 and ephrin-B2 are expressed in pituitary organogenesis (118,119). Ephrin-A5 is expressed in the ventral hypothalamus and developing posterior lobe.…”
Section: Cell Signaling Pathways Regulating Pituitary Stem Cellsmentioning
confidence: 99%
“…Our group reported CXCL12–CXCR4 signaling [11], which is important in the regulation of hematopoietic stem cells [17], between S100b-positive cells. Recently, Yoshida et al reported ephrin-B2 signaling in the same cell population [20]. A variety of signaling mechanisms may be required in order to maintain progenitor cells in the anterior pituitary progenitor niche.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a battery of new candidate markers has emerged from recent studies (extensively reviewed in Vankelecom 2010 andChen 2014), including the retinoic acid-producing retinal aldehyde dehydrogenase 1 (Raldh1; Fujiwara et al 2007) and the retinoic acid receptor Rarb (Vankelecom 2010;Vankelecom and Chen 2014); the transcription factors PRRX1 and PRRX2 (expressed in proliferating RP progenitor cells until cell-cycle exit and start of differentiation; Susa et al 2012); the cell-adhesion molecule cadherin-18 (expressed in the MZ in a different pattern than CDH1; Chauvet et al 2009); the coxsackievirus and adenovirus receptor (CAR; Chen et al 2013); the Kr€ uppel-like factor 6 (KLF6; Ueharu et al 2014); and the juxtacrine signaling molecule ephrin-B2 (Yoshida et al 2015). A number of the pituitary stem cell markers identified may be involved in constructing and maintaining the 3D network, in particular the cadherins, ephrins and CAR.…”
Section: Pituitary Stem Cells: Expanding Molecular Portrayalmentioning
confidence: 99%